Health Benefits of Ajwain (Tracyspermum ammi L.) (Global Journal of Medical Research, 2024)
Ajwain is highly valued in Unani as a gastrointestinal remedy and as an antiseptic. It is mixed with salt and hot water and brought after meals to alleviate bowel ache or colic and to enhance digestion. Ajwain is also a conventional treatment for cholera and fainting spells. Westerners typically use it for coughs and throat problems. It is also a component in mouthwashes and toothpastes because of its antiseptic homes. The volatile oil present within the seeds of ajwain is one of the predominant components accountable for imparting a normal taste, attributable to the presence of thymol. It also incorporates a cumene and terpene. The methanolic extracts of ajwain seeds possess herbal antioxidant properties. However, the acetone extract showed higher antioxidative hobby for linseed oil compared to synthetic antioxidants consisting of butylated hydroxy toluene and butylated hydroxy anisole. Ajwain oil exhibited a vast spectrum of fungitoxic behavior towards all tested fungi. Immediate research should focus on validating the antioxidant capability of herbs and spices after harvesting, in addition to testing their consequences on markers of oxidation.
Keywords: ajwain; unani; traditional